Changes in Phytoplankton Communities Along the Northern Antarctic Peninsula: Causes, Impacts and Research Priorities - Ferreira, Afonso; Costa, Raul R.; Dotto, Tiago S.; Kerr, Rodrigo; Tavano, Virginia M.; Brito, Ana C.; Brotas, Vanda; Secchi, Eduardo R.; Mendes, Carlos R. B. (Frontiers in Marine Science, 2020)
The Northern Antarctic Peninsula (NAP), located in West Antarctica, is amongst the most impacted regions worldwide by recent warming events. Its vulnerability to climate change has already led to an accumulation of severe changes along its ecosystems. This work reviews the current findings on impacts observed in phytoplankton communities occurring in the NAP, with a focus on its causes, consequences, and the potential research priorities for an integrated comprehension of the physical-biological coupling and climate perspective. Evident changes in phytoplankton biomass, community composition and size structure, as well as potential bottom-up impacts to the ecosystem are discussed. Surface wind, sea ice and meltwater dynamics, as the main drivers of the upper layer structure, are identified as the leading factors shaping phytoplankton. Short- and long-term scenarios are suggested for phytoplankton communities in the NAP, both indicating a future increase of the importance of small flagellates at the expense of diatoms, with potential devastating impacts for the ecosystem. Five main research gaps in the current understanding of the phytoplankton response to climate change in the region are identified: i) anthropogenic signal has yet to be disentangled from natural climate variability; ii) the influence of small-scale ocean circulation processes on phytoplankton is poorly understood; iii) the potential consequences to regional food webs must be clarified; iv) the magnitude and risk of potential changes in phytoplankton composition is relatively unknown; and v) a better understanding of phytoplankton physiological responses to changes in the environmental conditions is required. Future research directions, along with specific suggestions on how to follow them, are equally suggested. Overall, while the current knowledge has shed light on the response of phytoplankton to climate change, in order to truly comprehend and predict changes in phytoplankton communities there must be a robust collaboration effort integrating both Antarctic research programs and the whole scientific community under a common research framework.